Cannabinoid 1 Receptor Signaling on Hippocampal GABAergic Neurons Influences Microglial Activity - Ativie, Frank; Komorowska, Joanna A.; Beins, Eva; Albayram, Önder; Zimmer, Till; Zimmer, Andreas; Tejera, Dario; Heneka, Michael; Bilkei-Gorzo, Andras (Frontiers in Molecular Neuroscience, 2018)
Microglia, the resident immune cells of the brain, play important roles in defending the brain against pathogens and supporting neuronal circuit plasticity. Chronic or excessive pro-inflammatory responses of microglia damage neurons, therefore their activity is tightly regulated. Pharmacological and genetic studies revealed that cannabinoid type 1 (CB1) receptor activity influences microglial activity, although microglial CB1 receptor expression is very low and activity-dependent. The CB1 receptor is mainly expressed on neurons in the central nervous system (CNS)—with an especially high level on GABAergic interneurons. Here, we determined whether CB1 signaling on this neuronal cell type plays a role in regulating microglial activity. We compared microglia density, morphology and cytokine expression in wild-type (WT) and GABAergic neuron-specific CB1 knockout mice (GABA/CB1−/−) under control conditions (saline-treatment) and after 3 h, 24 h or repeated lipopolysaccharide (LPS)-treatment. Our results revealed that hippocampal microglia from saline-treated GABA/CB1−/− mice resembled those of LPS-treated WT mice: enhanced density and larger cell bodies, while the size and complexity of their processes was reduced. No further reduction in the size or complexity of microglia branching was detected after LPS-treatment in GABA/CB1−/− mice, suggesting that microglia in naïve GABA/CB1−/− mice were already in an activated state. This result was further supported by correlating the level of microglial tumor necrosis factor α (TNFα) with their size. Acute LPS-treatment elicited in both genotypes similar changes in the expression of pro-inflammatory cytokines (TNFα, interleukin-6 (IL-6) and interleukin 1β (IL-1β)). However, TNFα expression was still significantly elevated after repeated LPS-treatment in WT, but not in GABA/CB1−/− mice, indicating a faster development of tolerance to LPS. We also tested the possibility that the altered microglia activity in GABA/CB1−/− mice was due to an altered expression of neuron-glia interaction proteins. Indeed, the level of fractalkine (CX3CL1), a neuronal protein involved in the regulation of microglia, was reduced in hippocampal GABAergic neurons in GABA/CB1−/− mice, suggesting a disturbed neuronal control of microglial activity. Our result suggests that CB1 receptor agonists can modulate microglial activity indirectly, through CB1 receptors on GABAergic neurons. Altogether, we demonstrated that GABAergic neurons, despite their relatively low density in the hippocampus, have a specific role in the regulation of microglial activity and cannabinoid signaling plays an important role in this arrangement.